Molecular and Cellular Regulation of Toll-Like Receptor-4 Activity Induced by Lipopolysaccharide Ligands - Liaunardy-Jopeace, Ardiyanto; Gay, Nicholas J. (Frontiers in Immunology, 2014)
As well as being the primary signaling receptor for bacterial endotoxin or lipopolysaccharide Toll-like receptor 4 function is modulated by numerous factors not only in the context of microbial pathogenesis but also autoimmune and allergic diseases. TLR4 is subject to multiple levels of endogenous control and regulation from biosynthesis and trafficking to signal transduction and degradation. On the other hand regulation of TLR4 activity breaks down during Gram –ve sepsis leading to systemic damage, multi organ failure and death. In this article we review how TLR4 traffics from the early secretory pathway, the cis/trans Golgi to the cell surface and endolysosomal compartments. We will present evidence about how these processes influence signaling and can potentially lead to ligand independent constitutive activation that may contribute to pathogenesis in sepsis. We will also discuss how sustained signaling may be coupled to endocytosis and consider the potential molecular mechanisms of immuno-modulators that modify TLR4 signalling function including the cat allergen FelD1 and endogenous protein ligands such as the extracellular matrix protein tenascin C and calprotectin (MRP8/14).